Hak Atas Tanah Pada Kawasan Konservasi - Orias Reizal de Rooy; Hendrik Salmon; Reny Heronia Nendissa (PAMALI: Pattimura Magister Law Review, 2021)
Introduction: Regulation of the land control and land use on conservation areas, especially in coastal and coastal areas refers to the agrarian regulation in general, both for the benefit of the government and the public interest. The public interest is related to the rights that the State can give to its people for certain objects. Concerning the rights of the people, the state constitution guarantees the existence of the basic rights of the people, not only to the rights to land but also to other basic rights that are indeed held by the people and must be protected by the State.Purposes of the Research: Analyze the status of land rights in conservation areas and the legal consequences of land rights in conservation areas.Methods of the Research: The research methods used in this article is Normative Research, which is to examines and identify laws and regulations as well as legal concepts, especially about Land Rights on Conservation Areas to be the subject of study in finding the answers to the issues above.Results of the Research: The nature of the law which is always open and dynamic following the dynamics of changing community needs is expected to be able to answer the need for legal certainty itself through synchronization and harmonization of laws and regulations that explicitly regulate control and use of land in conservation areas that can guarantee certainty of community rights in the area. the coast.